The longest line on the map : the United States, the Pan-American Highway, and the quest to link the Americas - Rutkow, Eric (New York : Scribner, 2019)
Chronicles the epic quest to connect the Americas via the Pan American Highway, detailing how its construction and evolution reflected two centuries of divergent history.
Includes bibliographical references (pages 363-424) and index.
Keywords: Pan American Highway System; Roads -- America -- History; United States -- Foreign relations -- America; America -- Foreign relations -- United States